Security standardisation research : second International Conference, SSR 2015, Tokyo, Japan, December 15-16, 2015 : proceedings /: second International Conference, SSR 2015, Tokyo, Japan, December 15-16, 2015 : proceedings. ([2015]) - Unknown
No abstract available